Madness, distress and the politics of disablement / general editor, Helen Spandler, Jill Anderson, Bob Sapey. - Spandler, Helen, 1969-; Anderson, Jill (College teacher of Mental Health); Sapey, Bob (Policy Press, 2015)
An exploration of the relationship between madness, distress and disability, bringing together leading scholars and activists from Europe, North America, Australia and India.